Engaging youth with major depression in an exercise intervention with motivational interviewing. (October 2019) - Nasstasia, Yasmina; Baker, Amanda L.; Lewin, Terry J.; Halpin, Sean A.; Hides, Leanne; Kelly, Brian J.; Callister, Robin
Abstract: Background: Exercise has beneficial effects on depression; however, research is constrained by low program adherence. This paper investigates: 1) whether there are improvements in stage of change (exercise readiness) and exercise self-efficacy from before to after a brief motivational interviewing (MI) intervention designed to enhance program engagement among youth with major depressive disorder (MDD); and 2) any prospective association between baseline stage of change (exercise readiness) category and exercise program participation, retention and treatment outcomes. Methods: Selected pre- versus post-intervention and related secondary analyses based on pooled data from an initial pilot (n = 14) and subsequent two-armed RCT (n = 68). Participants were aged 15–25 years and met diagnostic criteria for MDD. Following psychological and physical fitness assessments, participants in the active treatment condition received a brief MI intervention followed by a supervised 12-week multi-modal exercise intervention. Results: Higher initial exercise readiness was significantly related to baseline weekly exercise participation and self-efficacy, with trend-level associations with behavioural activation. There was a trend level differential improvement in exercise readiness post MI, and a significant increase in self-efficacy among the intervention group. Post MI self-efficacy was also correlated with increased exercise participation. Clear post-intervention benefits were detected for most outcome measures; however, these were not differential by baseline stage of change category. Conclusion: Early MI based interventions increase exercise readiness and enhance self-efficacy, which may promote increased engagement and exercise adherence. Integrating MI as a prelude to exercise intervention shows promise as an effective engagement and treatment strategy among youth with MDD. Highlights: Motivational interviewing before exercise training promotes adherence to exercise. Motivational interviewing increases exercise readiness and enhances self-efficacy. Exercise self-efficacy is associated with increased exercise participation. Pre-treatment stage of change is not related to post treatment outcomes. Exercise training may be an effective adjunct for treating depression in youth.